Disability and the family : challenges, resources, and resilience - Claster, Patricia Neff; Blair, Sampson Lee (Emerald Publishing Limited, 2025)
Around the globe, most families will invariably have to face the challenges associated with the disability of a family member. A child with a learning disorder, an adult who has suffered a spinal cord injury, or an elderly family member who has lost their eyesight or hearing these are only a few of the many types of disabilities which both individuals and families face, every single day. Disability and the Family provides a broad examination of disability and the family. Including diverse theoretical and methodological submissions which explore the many issues pertaining to how families deal with disability issues, the chapters cover a wide array of topics, such as: family relationships and intellectual disability, learning disabilities and parenting, aging and developmental disabilities, coping and family caregivers, disability and family engagement, disability across the family life course, work and family challenges among parents of children with disabilities, physical mobility and marital quality, disability and sexuality, financial stressors and family relationships, and racial and ethnic variations in family care, among others. Acknowledging how disabilities can affect virtually all aspects of family life, creating emotional, social, financial, and even sexual challenges, this volume also emphasizes how families exhibit considerable resilience, even in seemingly overwhelming circumstances.
Includes index.
Keywords: People with disabilities -- Care.; Family & Relationships -- General.; Sociology.; Relationships and families: advice and issues.; elektronické knihy; electronic books